Intergenerational gender relations and household economy in coastal communities of Mercedes, Camarines Norte - Lamug, Corazon B. (Danyag :the UPV journal of humanities and social sciences, 2003)
"The study describes the dynamics of gender relations between two succeeding generations under conditions of different household economies in fishing communities. Five family pairs were selected consisting of a parental couple and on offspring couple from two barangays of Mercedes, Camarines Norte: Mambungalon and Pambuan. The method employed was narratives. The narratives centered on intergenerational gender relations in production endeavors, reproduction and community activities. The economy of each household was classified into low, moderate and high based assets and sources of income. Of the five pairs, one was classified as high, three were moderate and one household economy. The production relations in fishing centered on father-son. Fathers in high or moderate economies assisted their sons in acquiring their own boat and constructing their houses. Fathers in low economies were unable to extend assistance to their sons in terms of their fishing activities. The reproduction domain centered on the mother-daughter relation with extensive assistance being provided by the older generation on the younger one in the form of house maintenance, child care and financial loans for households emergencies. Parents of high or moderate household economies were in a better position to extend financial help to their children than those in low economies."